Professional development needs and decision-making of new graduate physiotherapists within Australian private practice settings - Zou, Yixin; Almond, Allexandra; Forbes, Roma (Physiotherapy theory and practice, 2023)
Professional development contributes to new graduate health professionals' transition into the workplace. Current literature indicates that new graduate physiotherapists are often underprepared to work within private practice settings, however little is known of their professional development needs to facilitate their transition. This study aimed to understand new graduate physiotherapists' perceived needs and decision-making for professional development within private practice settings. This study used a qualitative interpretative phenomenological approach. A sample of new graduate physiotherapists employed within private practice settings (n = 14) participated in semi-structured telephone interviews, after being selected through convenience and randomized sampling. Interview data was subject to thematic analysis. Four key themes emerged from the data: 1) practical and commercial relevance; 2) influence of self and others in decision-making; 3) professional development as a social construct; and 4) access is critical. New graduate physiotherapists expressed needs for practically and clinically relevant professional development within formal and informal settings, and this extended to non-clinical skills specific to private practice. Their decision-making was shaped by social influences and perceived barriers to access. This study has identified implications for employers and professional development providers to support and cater to new graduate physiotherapists' perceived needs for professional development, which may facilitate their transition into private practice.